SUSTAINABILITY ANALYSIS OF TRADITIONAL CAPTURE FISHERIES BASED ON LOCAL WISDOM AT LHOK KUALA GIGIENG, ACEH BESAR, INDONESIA - Makwiyah A. Chaliluddin; Nida Khafiyya; Thaib Rizwan; Djamali Rianjuanda; Muklis Muklis; Bustami Bustami; Sophia Listriani (Universitas Syiah Kuala, 2022)
This research focuses on the sustainability analysis of capture fisheries based on local wisdom in Lhok Kuala Gigieng. This study aims to analyze the sustainability status of capture fisheries and determine the factors that influence the sustainability of capture fisheries in Lhok Kuala Gigieng. The method used in this study is a descriptive method with survey techniques in data collection through questionnaires. The RAPFISH analysis uses four dimensions: ecological, economic, social, and institutional. This study indicates that the sustainability index score for the ecological dimension is in a good category, and the economic dimension of the sustainability index is in the medium category. Furthermore, it also shows that the social dimension of the sustainability index is in a good category, and the institutional dimension of the sustainability index is in a good category.